Neuro-Linguistic Programming Approach in the Preaching of Ustadz Rino Zeldeni - Dicky Nur Rahman; Akbar Trio Mashuri; Ali Nurdin (East Asian Journal of Multidisciplinary Research, 2023)
This research aims to examine more deeply how Ustadz Rino Zeldeni applies the basic concepts and techniques of Neuro-Linguistic Programming (NLP) in his preaching communication. The contribution of this research is to provide a new perspective on how the NLP approach can be applied in the context of Islam. In this study, Ustadz Rino Zeldeni can be used as an example of a da'i (Islamic preacher) who applies the NLP approach. The main concept of NLP is an approach used to improve communication, influence the thoughts and behaviors of the audience (mad'u), and his preaching concept refers to efforts to spread the teachings of Islam. This is a qualitative research method with a phenomenological approach. The results and implications of this study can provide guidance for D'ai with an approach through the 4 Pillars of NLP in improving preaching techniques such as helping the process of Islamic preaching communication, Ustadz Rino Zeldeni's Building Rapport, Nested Loops, Metaphors, and Chunking, which can provide input for the development of more innovative preaching in delivering the message of Islam in the future.